(3GdEfLjds
(3ChdgG (B:s
(3cQGQJg ddJhHg efg jSHbhge Edi edGFcI Gddg bGd cGf QLd dg EHfjf bGd GdChd efgeG jG Hfi CeVi Gdjhe EYed ai GdcQe s
(3BNQgG (B:s
(3adjcf dfG cdfG Cf fMXG HgG HfYeg QHfG EjShY GdeSjM hHYWag GdPi dg GdeLO hGdYR Edi CHGO GdOghQ Bejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdOjGfGJ GdCNQis